2023
DOI: 10.1021/acsami.3c00774
|View full text |Cite
|
Sign up to set email alerts
|

Direct Urea/H2O2 Fuel Cell with a Hierarchical Porous Nanoglass Anode for High-Efficiency Energy Conversion

Abstract: Direct urea/H 2 O 2 fuel cells (DUFCs) constitute a sustainable bifunctional energy conversion technique devoted to simultaneously eliminating environmental wastewater with urea and generating clean energy. However, exploring an efficient anode material for DUFCs still remains a huge challenge. In this work, a Ni−P hierarchical porous nanoglass (HPNG) catalytic electrode was developed via a low-cost, industrially available electrodeposition technique, which exhibits one of the best performances reported so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Pei et al [95] designed a Ni-P hierarchical porous nanoglass (Ni-P HPNG) using nickel foam as the substrate electrode via a two-step method, including the pulse electrodeposition and dealloying (Figure 7a-d). Then, the catalytic performance of the modified HPNG was compared to another electrode control (Figure 7e).…”
Section: Combining Ni With Non-metallic Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pei et al [95] designed a Ni-P hierarchical porous nanoglass (Ni-P HPNG) using nickel foam as the substrate electrode via a two-step method, including the pulse electrodeposition and dealloying (Figure 7a-d). Then, the catalytic performance of the modified HPNG was compared to another electrode control (Figure 7e).…”
Section: Combining Ni With Non-metallic Compoundmentioning
confidence: 99%
“…Pei et al [95] . designed a Ni‐P hierarchical porous nanoglass (Ni‐P HPNG) using nickel foam as the substrate electrode via a two‐step method, including the pulse electrodeposition and dealloying (Figure 7a–d).…”
Section: Ni‐based Catalyst For Dufcmentioning
confidence: 99%
“…Reproduced with permission. [225] Copyright 2023, American Chemical Society. d) The conversion process of urea at Ni 2 P@Ni foam anode.…”
Section: Direct Urea Fuel Cellmentioning
confidence: 99%
“…The battery test results confirmed that DUFCs could degrade urea in wastewater, and the urea degradation efficiency was ≈50% after 30 min. [225] However, H 2 O 2 at high temperatures easily decomposed into O 2 and water, which is detrimental to fuel utilization. This requires finding an oxidant that is more stable than H 2 O 2 and has a higher theoretical voltage than O 2 .…”
Section: Direct Urea Fuel Cellmentioning
confidence: 99%
See 1 more Smart Citation